Blockchain-based privacy-preserving remote data integrity checking scheme for IoT information systems. Issue 6 (November 2020) - Zhao, Quanyu; Chen, Siyi; Liu, Zheli; Baker, Thar; Zhang, Yuan
Abstract: Remote data integrity checking is of great importance to the security of cloud-based information systems. Previous works generally assume a trusted third party to oversee the integrity of the outsourced data, which may be invalid in practice. In this paper, we utilize the blockchain to construct a novel privacy-preserving remote data integrity checking scheme for Internet of Things (IoT) information management systems without involving trusted third parties. Our scheme leverages the Lifted EC-ElGamal cryptosystem, bilinear pairing, and blockchain to support efficient public batch signature verifications and protect the security and data privacy of the IoT systems. The results of the experiment demonstrate the efficiency of our scheme.